Hope-Based Intervention for Career Adaptability Among Final-Year Students - Ade Putri Juliati; Yulia Ayriza; Komang Tri Meika; Angelina Ekadiana Wera Marle; Nur Aini Triska Kiranti; Resdryan Sutriana (Jurnal Psikologi Perseptual, 2026)
Final-year university students are in a transitional stage toward entering the workforce, characterized by academic demands and career uncertainty, which necessitates a high level of career adaptability. This study aimed to examine the effectiveness of a hope-based intervention in enhancing career adaptability among final-year students. A quasi-experimental design with a non-equivalent control group pretest–posttest design was employed. The study population consisted of final-year university students, with a sample of 12 participants selected through purposive sampling based on predetermined criteria. Participants were assigned to either an experimental group (n = 6) or a control group (n = 6). The experimental group received a hope-based intervention, while the control group did not receive any treatment. Data were collected using the Career Adapt-Abilities Scale (CAAS) and analyzed using paired-samples t-tests and independent-samples t-tests. The results indicated that the mean career adaptability score of the experimental group increased from 101.00 to 113.00, whereas the mean score of the control group decreased from 94.00 to 92.00. Statistical analyses revealed a significant improvement in career adaptability within the experimental group (t = −3.098, p= .027) and a significant difference between the experimental and control groups following the intervention (t = 4.916, p= .001). These findings suggest that the Brief Hope Intervention is effective in enhancing the career adaptability of final-year university students. The study concludes that hope-based interventions can serve as a valuable approach for fostering career adaptability and strengthening career development services in higher education settings. Mahasiswa tingkat akhir berada pada fase transisi menuju dunia kerja yang ditandai oleh tuntutan akademik dan ketidakpastian karier, sehingga memerlukan kemampuan adaptabilitas karier yang optimal. Penelitian ini bertujuan untuk menguji efektivitas intervensi hope dalam meningkatkan career adaptability pada mahasiswa tingkat akhir. Penelitian menggunakan desain quasi-experimental dengan non-equivalent control group pretest–posttest design. Populasi penelitian adalah mahasiswa tingkat akhir, dengan sampel sebanyak 12 mahasiswa yang dipilih menggunakan teknik purposive sampling berdasarkan kriteria tertentu. Partisipan dibagi ke dalam kelompok eksperimen (n = 6) dan kelompok kontrol (n = 6). Kelompok eksperimen diberikan intervensi hope, sedangkan kelompok kontrol tidak memperoleh perlakuan. Data dikumpulkan menggunakan Career Adapt-Abilities Scale (CAAS) dan dianalisis dengan paired sample t-test serta independent sample t-test. Hasil menunjukkan bahwa rata-rata skor career adaptability pada kelompok eksperimen meningkat dari 101,00 menjadi 113,00, sedangkan kelompok kontrol menurun dari 94,00 menjadi 92,00. Uji statistik menunjukkan peningkatan yang signifikan pada kelompok eksperimen (t = −3,098; p= 0,027) dan perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol setelah intervensi (t = 4,916; p= 0,001). Temuan ini menunjukkan bahwa Brief Hope Intervention efektif dalam meningkatkan career adaptability mahasiswa tingkat akhir. Temuan ini menyimpulkan bahwa intervensi hope efektif dalam mengembangkan adaptabilitas karier mahasiswa tingkat akhir dan berkontribusi pada penguatan pendekatan intervensi psikologis berbasis hope dalam layanan pengembangan karier di perguruan tinggi.